Analysis of possibility of the high-duty cast iron using for production of diesel forcers - A. N. Krutilin; V. S. Losj; T. V. Matjushinets; M. V. Osadnik (Литьë и металлургия)
There is given the analysis of the possibility of change of aluminium piston alloys by high-duty cast iron with globular or vermicular form of graphite.